1988
DOI: 10.1093/bja/60.5.570
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous Oxide and Day-Case Laparoscopy: Effects on Nausea, Vomiting and Return to Normal Activity

Abstract: Patients admitted for day-case laparoscopy were assigned randomly to receive nitrous oxide-oxygen or oxygen, with enflurane, during a standard anaesthetic technique. Postoperative morbidity, in particular nausea and vomiting, and ability to resume normal activity were assessed over the ensuing 48 h. Supplementary administration of propofol during the operative procedure was required significantly more often (P less than 0.05) in the absence of nitrous oxide. There was no significant difference in the incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…All the reported studies on PONV after N 2 O/volatile anesthetic (enflurane or isoflurane) in gynecologic laparoscopic surgery compared a single FI of N 2 O, usually in the range of 66%-70%, with control. 20,21,23,24 The results from this study agree with those of Felts et al who demonstrated that PONV is increased from 9.3% in air/oxygen (FI O 2 33%) to 29.2% with 66% of N 2 O in oxygen after enflurane anesthesia for outpatient gynecologic laparoscopy (P Ͻ 0.001). 21 Contrary to our study, Hovorka et al did not find significant differences in the incidence of PONV among three groups of patients anesthetized with either isoflurane or enflurane with 70% N 2 O in oxygen, and isoflurane without N 2 O, after gynecological laparoscopy.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…All the reported studies on PONV after N 2 O/volatile anesthetic (enflurane or isoflurane) in gynecologic laparoscopic surgery compared a single FI of N 2 O, usually in the range of 66%-70%, with control. 20,21,23,24 The results from this study agree with those of Felts et al who demonstrated that PONV is increased from 9.3% in air/oxygen (FI O 2 33%) to 29.2% with 66% of N 2 O in oxygen after enflurane anesthesia for outpatient gynecologic laparoscopy (P Ͻ 0.001). 21 Contrary to our study, Hovorka et al did not find significant differences in the incidence of PONV among three groups of patients anesthetized with either isoflurane or enflurane with 70% N 2 O in oxygen, and isoflurane without N 2 O, after gynecological laparoscopy.…”
Section: Discussionsupporting
confidence: 90%
“…Sengupta and Plantevin reported results similar to Lonie and Harper, but their study was under-powered, with a smaller number of patients (64), which resulted in a nonstatistically significant difference between the N 2 O group and oxygen group, 33% versus 12.9%, respectively. 24 Results from the IMPACT study suggest that omitting N 2 O in a multimodal PONV prophylaxis strategy further decreases the incidence of PONV by about 12%, if a volatile anesthetic is used. 29 However, the study did not address the dose-response relationship of N 2 O.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrous oxide has been associated with bowel distention (17) and with delay in return of bowel function after colonic surgery (18). However, in prospective randomized clinical trials, the use of nitrous oxide during laparoscopy was reported to have no influence on the operative conditions, on the development of bowel distention (191, on the incidence of postoperative nausea and vomiting (201, or on postoperative analgesia requirements (21).…”
Section: Discussionmentioning
confidence: 99%
“…Korttila et aU 119 ] also concluded that nitrous oxide did not contribute to the occurrence of nausea and vomiting following isoflurane anaesthesia for gynaecological procedures among 110 patients. Also, Sengupta and Plantevin [120] followed 64 patients postoperatively for 48 hours and found no difference in PONY between the groups with nitrous oxide or without nitrous oxide. Hovorka and Korttila [121] did a study in 150 inpatients scheduled for elective gynaecological surgery.…”
Section: Nitrous Oxidementioning
confidence: 95%